Introducción acerca de las implicaciones del Estado de Derecho en su relación con el concepto de responsabilidad patrimonial - Rodríguez Lozano, Luis Gerardo (2016)
The author makes an inquiry into the evolution of the State as a product of what is known as the Modern State. The study focuses on the historical and legal aspects of the concept of the Rule of Law as a product of the Modern State, in order to analyze the construction and institutionalization of a system of asset liability of the State.